PENGARUH FAKTOR DEMOGRAFI DAN INVESTASI SWASTA TERHADAP PERTUMBUHAN EKONOMI KOTA SAMARINDA - Nurul Fitriani; Theresia Militina; Aji Sofyan Effendi (Jurnal Ekonomi Pembangunan, 2012)
Research purpose were to knowing (1) the significant effect of the rate of population growth, population density, dependency ratio, the Human Development Index (HDI) simulatneously on economic growth in Samarinda. (2) Determine the dominant effect of the rate of population growth, population density, dependency ratio, the Human Development Index (HDI) to economic growth of Samarinda. This research uses analytic descriptive with the survey method and the characteristic of research was to explain that aims to test different variables associated with research hypotheses had proposed. Results above could be explained that the population growth variable has a negatively on economic growth, which indicates the increasing population would likely reduce economic growth. Population density variable has a positive and significant impact on economic growth, which indicates that the higher the population density of an area, the higher the economic growth. Dependency ratio variable has a negative sign for economic growth, which indicates that the higher the value of the dependency ratio, the lower the economic growth. Human Development Index (HDI) has a positive and significant sign of economic growth, indicates that the higher the value of the HDI, the higher the economic growth.